Analisis Pendapatan Asli Daerah Sektor Perusahaan Daerah di Kabupaten Lamongan - Abid Muhtarom (Universitas Negeri Malang, 2016)
Regional Income is income earned something of a region directly. The greater the income the greater the area of regional development can be implemented in accordance with the regional budget. In order to compile this study, the authors conducted a descriptive research with a qualitative approach. Namely to describe the phenomenon that is qualitatively with expectations could potentially open-interpretation of subjective interpretation. By interpreting the data on the reception pattern profit company owned by the regional implications to increase revenue in the budget Lamongan District Government. This research was conducted in the district of Lamongan in January to June 2015. Based on the results of the analysis of the calculation of the contribution that profit enterprises in the year 2010 to the year 2014 still has contribution but not optimal. This means that the profit enterprises still contribute to regional revenue Lamongan though not completely.Keywords: Regional Income, Local Company, Regionally-Owned Enterprises